The different central nervous system efficacy among gefitinib, erlotinib and afatinib in patients with epidermal growth factor receptor mutation-positive non-small cell lung cancer - Jung, Hyun Ae (Transl Lung Cancer Res, 2020)
BACKGROUND: Brain metastasis is common in non-small cell lung cancer (NSCLC) and has an even higher incidence in epidermal growth factor receptor (EGFR)-mutant cancers. Although EGFR tyrosine kinase inhibitors (TKIs) are effective against brain metastases, it is unknown which first- or second-generation EGFR TKI is most effective. METHODS: Patients treated with first-line gefitinib, erlotinib, or afatinib for advanced EGFR-mutant NSCLC were included. The efficacy against brain metastasis was evaluated by comparing the response rates of measurable and non-irradiated brain metastases, central nervous system progression-free survival (CNS-PFS), and the cumulative incidence of CNS failure. RESULTS: Among the 559 patients who received EGFR-TKIs (gefitinib, n=299; erlotinib, n=93; afatinib, n=167), 198 had initial brain metastasis before starting EGFR-TKIs. The CNS response rates of gefitinib, erlotinib, and afatinib were 64.7%, 68.2%, and 72.9%, respectively (P=0.78). In the overall study population, irrespective of initial CNS metastasis, the median CNS-PFS was 17.3 months for gefitinib, 12.4 months for erlotinib, and 23.3 months for afatinib (P<0.001). In multivariate analysis for CNS-PFS, the hazard ratio (HR) of afatinib was 0.63 (95% CI, 0.47–0.83) compared with gefitinib or erlotinib. In the competing risk analysis for cumulative incidence of CNS failure, afatinib showed a lower cumulative incidence of CNS failure compared with gefitinib or erlotinib after adjusting for both EGFR mutation type and preexisting CNS metastases (HR 0.51, 95% CI, 0.34–0.75, P=0.0007). CONCLUSIONS: Through there are some limitation as a retrospective study, afatinib showed similar CNS response rates, superior CNS-PFS and cumulative incidence of CNS failure, compared with gefitinib or erlotinib